EVALUATION OF ECO-EXTRACTION METHODS OF ANTIOXIDANTS AND THEIR ACTIVITIES FROM RETAMA RAETAM TWIGS - zaoui, Oussama; Oughlissi-Dehak, karima; Bouziane, Mebarka; boudou, farouk; zaoui, fatiha; Benras, Amina; Hadj-Mahammed, Mahfoud; sehmi, abd elghani (Polish Journal of Natural Sciences, 2023)
The purpose of this study was to compare the effectiveness of five different conventional (maceration, reflux, and soxhlet) and non-conventional (microwave-assisted extraction (MAE), and ultrasonic-assisted extraction (UAE)) techniques of extracting secondary metabolites (total phenols, total flavonoid and total condensed tannin Contents) and their antioxidant activity (2,2-diphényl 1-picrylhydrazyle free radical-scavenging ability, and ferric reducing antioxidant power assay) obtained from Retama Raetam twigs using two green solvents (water and ethanol 70%). The aqueous and hydro-ethanolic extracts obtained by MAE revealed the highest contents of total phenols (168.24 ± 0.79 and 182.6 ± 1.29 mg EAG / g DR, respectively), and flavonoids (12.,28 ± 0.92 and 39.97 ± 1.11 mg EC/ g DR, respectively), and exhibited a significant capacity to scavenge free radicals with median inhibitory concentrations (IC50) of 0.45± 0.75 and 0.34 ± 0.39 mg/mL, and a significant iron reducing power with median effective concentrations (EC50) of 0.358 ± 0.2 and 0.28 ± 0.1 mg/mL for the aqueous and hydro-ethanolic extracts, respectively. The MAE was proven to be the most efficient extraction technique for the extraction of antioxidants from Retama Raetam twigs.